2013
DOI: 10.1038/ni.2730
|View full text |Cite
|
Sign up to set email alerts
|

Defective sphingosine 1-phosphate receptor 1 (S1P1) phosphorylation exacerbates TH17-mediated autoimmune neuroinflammation

Abstract: Sphingosine-1-phosphate (S1P) signaling regulates lymphocyte egress from lymphoid organs into systemic circulation. Sphingosine phosphate receptor 1 (S1P1) agonist, FTY-720 (Gilenya™) arrests immune trafficking and prevents multiple sclerosis (MS) relapses. However, alternative mechanisms of S1P-S1P1 signaling have been reported. Phosphoproteomic analysis of MS brain lesions revealed S1P1 phosphorylation on S351, a residue crucial for receptor internalization. Mutant mice harboring a S1pr1 gene encoding phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
105
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 143 publications
(116 citation statements)
references
References 45 publications
9
105
0
2
Order By: Relevance
“…However, T cell S1P 1 may also regulate the activation and differentiation status of these immune cells. Deletion of T cell S1P 1 signifi cantly suppresses the ability of these cells to be polarized to T-helper (Th)17 in vitro ( 72 ). Conversely, when EAE was induced in mice expressing an internalizationdefective S1P 1 (S5A), this signifi cantly increased polarization of T cells to the Th17 phenotype resulting in increased disease pathology and immune cell infi ltration into the CNS ( 72 ).…”
Section: Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…However, T cell S1P 1 may also regulate the activation and differentiation status of these immune cells. Deletion of T cell S1P 1 signifi cantly suppresses the ability of these cells to be polarized to T-helper (Th)17 in vitro ( 72 ). Conversely, when EAE was induced in mice expressing an internalizationdefective S1P 1 (S5A), this signifi cantly increased polarization of T cells to the Th17 phenotype resulting in increased disease pathology and immune cell infi ltration into the CNS ( 72 ).…”
Section: Immune Systemmentioning
confidence: 99%
“…Deletion of T cell S1P 1 signifi cantly suppresses the ability of these cells to be polarized to T-helper (Th)17 in vitro ( 72 ). Conversely, when EAE was induced in mice expressing an internalizationdefective S1P 1 (S5A), this signifi cantly increased polarization of T cells to the Th17 phenotype resulting in increased disease pathology and immune cell infi ltration into the CNS ( 72 ). S1P 1 is also expressed on CD4 T cells isolated from human rheumatoid arthritis patients ( 73 ).…”
Section: Immune Systemmentioning
confidence: 99%
“…I45T and G305C mutants phenocopy a S1P 1 (S5A) mutant in which fi ve serine residues in the carboxyl-terminal region are substituted with alanine. Recently, our group reported that S1P 1 (S5A) mutant mice showed enhanced autoimmunity and developed severe experimental autoimmune encephalomyelitis ( 26 ). Thus, impairment of the receptor internalization in I45T and G305C mutants may result in increased autoimmunity as observed in S1P 1 (S5A) mice, raising a possibility that these SNPs can be potential risk factors for autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…FTY720 inhibits the egress of lymphocytes from secondary lymphoid organs by inducing internalization and irreversible S1P 1 degradation in the proteasome ( 25,30 ). Recently, our group showed that mutant mice harboring the S1PR1 gene encoding phosphorylation-defi cient, and as such endocytosis-defi cient, receptors [S1P 1 (S5A)] developed severe experimental autoimmune encephalomyelitis due to T helper 17 cell-mediated autoimmunity, both in the peripheral immune system and the nervous system ( 26 ). This S1P 1 (S5A) receptor shows resistance to FTY720-induced degradation both in vivo and in vitro ( 25,30 ).…”
Section: Diminished Effi Cacy Of Fty720 On I45t and G305c Mutantsmentioning
confidence: 99%
See 1 more Smart Citation